2016
DOI: 10.1118/1.4967265
|View full text |Cite
|
Sign up to set email alerts
|

Computer aided prognosis for cell death categorization and prediction in vivo using quantitative ultrasound and machine learning techniques

Abstract: The technology developed in this study addresses a gap in the current standard of care by introducing a quality control step that generates potentially actionable metrics needed to enhance treatment decision-making. The study establishes a noninvasive framework for quantifying levels of cancer treatment response developed preclinically in tumors using QUS imaging in conjunction with machine learning techniques. The framework can potentially facilitate the detection of refractory responses in patients to a cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…QUS spectral parameters were acquired from the normalized, frequency-dependent power spectrum of the RF data. A sliding window analysis was performed on a pixel by pixel basis within the ROI with a window size of 2 x 2 mm 2 to include approximately 10 ultrasound wavelengths and overlap in both the lateral and axial direction of 92% [23,26,29,30].…”
Section: Qus Data Processingmentioning
confidence: 99%
“…QUS spectral parameters were acquired from the normalized, frequency-dependent power spectrum of the RF data. A sliding window analysis was performed on a pixel by pixel basis within the ROI with a window size of 2 x 2 mm 2 to include approximately 10 ultrasound wavelengths and overlap in both the lateral and axial direction of 92% [23,26,29,30].…”
Section: Qus Data Processingmentioning
confidence: 99%
“…QUS parameters have been demonstrated to be sensitive to subtle microstructural characteristics and alterations occurring in tissue due to biological responses and tissue morphology resulting from disease or treatment. These have been previously demonstrated in preclinical studies (14,27,(28)(29)(30) and in a clinical setting including patients with prostate cancer [disease detection (31), and extent of the disease (17)], as well as colorectal, gastric, and breast cancer patients to detect lymph node metastases (12,32). Furthermore, QUS can be used in clinic to evaluate cancer treatment response and help clinicians adapt cancer therapies and exchange ineffective treatment therapies at an early stage (12,25,26,33).…”
Section: Discussionmentioning
confidence: 96%
“…One of these techniques is quantitative ultrasound spectroscopy (QUS), which was first promulgated by Lizzi and colleagues in the early 1980s (13). QUS can provide quantitative information related to tissue characteristics using standard ultrasound systems (12), and allows differentiation of tissue microstructures by analyzing the radiofrequency (RF) signals backscattered from biological tissues (14). It is independent of instrument settings through a signal normalization process that uses a reference phantom with known backscatter and attenuation coefficients (12,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous apoptosis is a mitochondrial-activated apoptosis process regulated by the Bcl-2 protein family. It is reported that low-frequency ultrasound combined with microbubbles can promote apoptosis of prostate cancer cells, liver cancer cells, ovarian cancer cells, glioma cells, and human leukemia cells (Lagneaux et al, 2002;Bai et al, 2016;Gangeh et al, 2016), and reduce damage to normal tissues. Hou et al (2017) reported that low-frequency ultrasound combined with microbubbles can affect the hypoxic response of a tumor, inhibit tumor growth, and promote cell apoptosis.…”
Section: Inducing Autophagy and Apoptosis Of Tumor Cells Inhibiting mentioning
confidence: 99%